The Effect of Intelligence Numeric, Learning Discipline and Learning Motivation on Formative Test Results - Muh. Aripin Nurmantoro; Dedy Yusuf Aditya; Dede Irawan (EduResearch Mitra Inovasi, 2019)
The purpose of this study was to determine the direct effect and indirect influence of a variable. The research data was processed and analyzed using path analysis method. Conclusions are obtained (1) There is a significant direct effect of intelligence numeric on the results of formative tests; (2) There is a significant direct effect of learning discipline on the results of formative tests; (3) There is a significant direct effect of learning motivation on the results of formative tests; (4) There is a significant direct effect of intelligence numeric on learning motivation; (5) There is a significant direct influence of intelligence numericalon learning discipline; (6) There is a significant direct effect of learning discipline on learning motivation; (7) There is no significant indirect effect of intelligence numericon motivation to learn through learning discipline; (8) There is no significant indirect effect of intelligence numeric on the results of formative tests through learning discipline; (9) There is no significant indirect effect of intelligence numeric on the results of formative tests through learning motivation; and (10) There is no significant indirect effect of intelligence numeric on the results of formative tests through learning discipline and learning motivation.